The ESG-tax avoidance nexus in SOEs: Do investment, strategy, and political ties matter - Khairin, Mochamad Yahdi; Firmansyah, Amrie (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study investigates the effects of the investment opportunity set, prospector business strategy, and political connections on tax avoidance, with ESG disclosure playing a potential moderating role.Design/Methodology/Approach: Using an unbalanced panel of 127 observations from 32 non-financial State-owned enterprises (SOEs), listed and non-listed on the IDX, this research utilizes secondary data from financial and sustainability reports for 2019–2023. Hypothesis testing was conducted via multiple linear regression at a 10% significance level.Research findings: This study indicates that only the prospector business strategy positively influences tax avoidance, while ESG (Environmental, Social, and Governance) disclosure dampens this relationship. In contrast, the investment opportunity set and political connections do not significantly affect tax avoidance, and ESG disclosure does not strengthen nor weaken these relationships.Theoretical contribution/ Originality: This study enhances the application of stakeholder theory, highlighting how ESG disclosure aligns with the ethical and transparent behavior expected in corporate tax strategies.Practitioner/Policy implication: Effective ESG disclosures encourage companies to adopt ethical tax practices, reduce aggressive tax avoidance, and foster transparency.Research limitation/Implication: Limited data on non-listed SOEs, as only 12 firms provided comprehensive financial and sustainability reports, restricts the sample size for these entities.